2007
DOI: 10.1148/radiol.2441060790
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed Gastric Artery Chemical Embolization for Modulation of Systemic Ghrelin Levels in a Porcine Model: Initial Experience

Abstract: Use of GACE can result in increased or suppressed ghrelin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 19 publications
2
67
0
Order By: Relevance
“…Relatively recently, a percutaneous procedure has been described by Arepally et al (12,13), which directly targets the gastric fundus and its functionality. In these investigations, gastric artery chemical embolization (or GACE) was performed by injecting a liquid sclerosing agent, sodium morrhuate, into the main left gastric artery with fluoroscopic guidance.…”
Section: Bariatric Embolizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively recently, a percutaneous procedure has been described by Arepally et al (12,13), which directly targets the gastric fundus and its functionality. In these investigations, gastric artery chemical embolization (or GACE) was performed by injecting a liquid sclerosing agent, sodium morrhuate, into the main left gastric artery with fluoroscopic guidance.…”
Section: Bariatric Embolizationmentioning
confidence: 99%
“…In these investigations, gastric artery chemical embolization (or GACE) was performed by injecting a liquid sclerosing agent, sodium morrhuate, into the main left gastric artery with fluoroscopic guidance. These studies showed in a porcine model that gastric artery chemical embolization can suppress systemic levels of ghrelin in the short term (12,13). However, liquid sclerosing agents are highly toxic and are difficult to administer via vascular delivery; therefore, they are not a clinically viable option.…”
Section: Bariatric Embolizationmentioning
confidence: 99%
“…GACE-treated swine (n ϭ 5) underwent embolization with 125 g of sodium morrhuate (American Regent, Shirley, NY), while control animals (n ϭ 5) underwent a sham embolization with saline. The dosage was based on results of our prior experiments involving various dosages during GACE (12). After an overnight fast, two blood samples from each animal for baseline ghrelin analysis were obtained simultaneously immediately prior to the procedure.…”
Section: Animal Model and Baseline Blood Samplesmentioning
confidence: 99%
“…was based on results of our prior doseescalating trial for GACE (12). GACEtreated swine that had multiple accessory gastric arteries to the fundus underwent injection of sodium morrhuate into all the accessory gastric arteries, with the volume of sodium morrhuate divided equally among arteries.…”
Section: Experimental Studies: Gastric Artery Chemical Embolization Amentioning
confidence: 99%
See 1 more Smart Citation